2015
DOI: 10.1093/mnras/stv395
|View full text |Cite
|
Sign up to set email alerts
|

Evidence of tidal distortions and mass-loss from the old open cluster NGC 6791

Abstract: We present the first evidence of clear signatures of tidal distortions in the density distribution of the fascinating open cluster NGC 6791. We used deep and wide-field data obtained with the Canada-France-Hawaii-Telescope covering a 2 • ×2 • area around the cluster. The two-dimensional density map obtained with the optimal matched filter technique shows a clear elongation and an irregular distribution starting from ∼ 300 ′′ from the cluster center. At larger distances, two tails extending in opposite directio… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
53
1

Year Published

2015
2015
2020
2020

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 52 publications
(56 citation statements)
references
References 48 publications
2
53
1
Order By: Relevance
“…To derive an estimate of the cluster initial mass, several constants characterising the cluster and the environment need to be adopted. To evaluate the equation (1) of Dalessandro et al (2015), we use t = 1.6 ± 0.1 Gyr for the age of the cluster, and the three mass estimates derived above: m 1 = 1820 ± 620M (Sect. 6), m 2 = 1880 ± 820M (Sect.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…To derive an estimate of the cluster initial mass, several constants characterising the cluster and the environment need to be adopted. To evaluate the equation (1) of Dalessandro et al (2015), we use t = 1.6 ± 0.1 Gyr for the age of the cluster, and the three mass estimates derived above: m 1 = 1820 ± 620M (Sect. 6), m 2 = 1880 ± 820M (Sect.…”
Section: Discussionmentioning
confidence: 99%
“…To characterise the mass loss due to the stellar evolution (equation (2) in Dalessandro et al (2015)), we use the metallicity Z = 0.02 (the coefficients given in Table 1 of Lamers et al (2005), which is sufficiently close to the value of 0.025 estimated here. The tidal mass loss is characterised by the dissolution timescale t 0 = 3.3 +1.4 −1.0 Myr.…”
Section: Discussionmentioning
confidence: 99%
“…In addition we have found that NGC 6362 is the first cluster where the radial distributions of its MPs show no significant radial difference up to its tidal radius. We interpreted such unexpected evidence as the result of a very advanced dynamical evolution and possibly of a significant mass-loss due to interactions with the Galactic disk and potential well (see Dalessandro et al 2015).…”
Section: Introductionmentioning
confidence: 97%
“…As clusters age, the expulsion of gas by stellar feedback as well as dynamical interactions between stars and binary systems in the cluster soften its gravitational potential, leading to their expansion and to their partial or total dissolution into the field of their host galaxy (e.g., Spitzer & Harm 1958;Parker & Meyer 2012;Parker & Dale 2013;Dib et al 2011a,b;Dib 2011;Dib et al 2013;Pfalzner & Kaczmarek 2013;Brinkmann et al 2017). Clusters can also be ⋆ E-mail, SD: sami.dib@gmail.com † Royal Society Dorothy Hodgkin Fellow disrupted by close encounters with giant molecular clouds as they orbit the Galactic centre (e.g., Gieles et al 2006) or by being subjected to strong tidal fields (e.g., Dalessandro et al 2015;Zhai et al 2017;Martinez-Medina et al 2017). …”
Section: Introductionmentioning
confidence: 99%